The British and the German financial sectors in the wake of the crisis: size, structure and spatial concentration - Wójcik, D; MacDonald-Korth, D (Oxford University Press, 2015)
We use employment data for 2008–2012 to analyse the impact of the subprime and Eurozone crises on the British and German financial sector. In the UK, the sector contracted and its spatial concentration increased across regions and urban hierarchy, with London as the sole winner. In Germany there has been no contraction overall, and no significant change in the spatial distribution of financial employment. We argue that while in both countries forced consolidation and financial re-regulation have acted as centripetal forces, in Germany they have been offset by strong regional and local banking, underpinned by a decentralized state.